Relações de amizade de adultos com osteogênese imperfeita. - Almeida, Isabela Medeiros de (2020)
Almeida, I. M. (2020). Friendship relationships of people with Osteogenesis Imperfecta. Master‟s Dissertation. Psychology Post Graduattion Program of Federal University of Espírito Santo, Brazil. ABSTRACT The Imperfecta Osteogenesis (IO), best-known